Surface characterizationofself-assembled NCu nanostructures - Cristina, Lucila Josefina (2012)
We report on the process of low energy nitrogen implantation and annealing of a copper surface. Through auger electron spectroscopy we study the nitrogen diffusion features as a function of the substrate temperature. With STM and LEIS we characterize the surface mofphology and the electronic sturcturi es analyzed with ARUPS.